PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN KEPALA SEKOLAH (Studi Pada MTs Swasta Kecamatan Winong Kabupaten Pati) - Muhamad Anis, 12.52.02.0227; Sutomo, Y. (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of Competence and Motivation on Teacher Performance moderated Principal Leadership (Studies in Teacher Private MTs Winong District of Pati regency). This study included in the quantitative research using survey method through descriptive analysis approach. This study whit a census tehnic where the sample size is equal to the population of as many as 115 teachers, while the data is processed as many as 102 teachers. Measurements using a Likert scale with 5 (five) alternative answers. Test instruments used are validity and reliability. Normality Test (1 Sample-KS) Classical Assumption Test (test heterokedastisitas) The test model used is the coefficient of determination (R2) and the F test (Goodness of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Competence positive and significant impact on teacher performance, (ii) Motivation positive and significant impact on teacher performance, (iii) Leadership Principal positive and significant impact on teacher performance, (iv) Effect Competence of the Teacher Performance is not moderated Leadership Principal, (iv) Effect of Motivation on teacher performance is not moderated Leadership PrincipalKeywords: Competence, Motivation, Leadership Principal and Teacher Performance